Atmospheric oxidation reactions of imidazole initiated by hydroxyl radicals: kinetics and mechanism of reactions and atmospheric implications. Issue 16 (5th April 2019) - Safaei, Zahra; Shiroudi, Abolfazl; Zahedi, Ehsan; Sillanpää, Mika
Abstract : The atmospheric oxidation mechanism of imidazole initiated by hydroxyl radicals is investigated via OH-addition and H-abstraction pathways by quantum chemistry calculations at the M06-2X/aug-cc-pVTZ level of theory coupled with reaction kinetics calculations using statistical Rice–Ramsperger–Kassel–Marcus (RRKM) theory and transition state theory (TST). Abstract : The atmospheric oxidation mechanism of imidazole initiated by hydroxyl radicals is investigated via OH-addition and H-abstraction pathways by quantum chemistry calculations at the M06-2X/aug-cc-pVTZ level of theory coupled with reaction kinetics calculations using statistical Rice–Ramsperger–Kassel–Marcus (RRKM) theory and transition state theory (TST). It was found that OH addition proceeds more rapidly than H-abstraction by several orders of magnitude. Moreover, H-abstraction reactions with submerged barriers exhibit positive temperature dependence. Effects of reaction temperature and pressure on the reaction between imidazole and OH radicals are studied by means of RRKM calculations. Effective rate coefficients involve two-step mechanisms. According to the experiment, the obtained branching ratios show that the kinetically most efficient process corresponds to OH addition onto a carbon atom which is adjacent to a nitrogen atom having a lower energy barrier. These ratios also reveal that the regioselectivity of the oxidation reaction decreases with increasing temperatures and decreasing pressures. Because of negative activation energies, pressures larger than 100 bar are required to reach the high pressure limit. The atmospheric lifetime of imidazole in the presence of OH radicals is estimated to be ∼4.74 days, based on the calculated overall kinetic rate constant of 1.22 × 10 −12 cm 3 molecule −1 s −1 at a pressure of 1 bar and nearly ambient temperature. NBO analysis demonstrates that the calculated energy barriers are dictated by charge transfer effects and aromaticity changes because of the delocalization of nitrogen lone pairs to empty π* orbitals.